Towards Starting a Hand Transplant Unit and Achieving Success in a Hand Transplant: The Standard Operating Procedure - Puri, Vinita; Venkateshwaran, Narasiman; Shrotriya, Raghav; Chalwade, Chandrashekhar (Archives of Plastic Surgery, 2024)
Vascularized Composite Tissue Allotransplantation (VCA) allows replacement of lost body parts from brain-dead donors. These surgeries are laborious, time-intensive, and require vast planning. With the advent of better immunosuppressants, VCA will increasingly play an important role in the reconstructive field. In this paper, the authors share their standard operating protocol created after much deliberation.
Keywords: forearm; hand; hand transplant; vascularized composite allotransplantation; microsurgery; amputation; surgical; standard operating protocol